2019
DOI: 10.1080/02673037.2019.1584665
|View full text |Cite
|
Sign up to set email alerts
|

Understanding changing housing aspirations: a review of the evidence

Abstract: This article reviews the literature on changing housing aspirations and expectations in contemporary housing systems. It argues that there is a conceptual and definitional gap in relation to the term 'housing aspirations', as distinct from expectations, preferences, choices and needs. The article sets out working definitions of these terms, before discussing the evidence on changing housing (and related) systems. Emerging research has begun to consider whether trends such as declining homeownership, affordabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 69 publications
0
33
0
3
Order By: Relevance
“…Households make assessments based on expectations regarding future housing value or living satisfaction. This ties into the insight that aspirations are aspirations are dialectically constituted by social conditions and material reality indicated by existing housing research (Crawford & McKee, 2018;Preece et al, 2019). Social imaginaries around homeownership, autonomy and self-sufficiency are influential in shaping self-building practices (Soaita, 2015).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Households make assessments based on expectations regarding future housing value or living satisfaction. This ties into the insight that aspirations are aspirations are dialectically constituted by social conditions and material reality indicated by existing housing research (Crawford & McKee, 2018;Preece et al, 2019). Social imaginaries around homeownership, autonomy and self-sufficiency are influential in shaping self-building practices (Soaita, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…The constitution of aspirations is not exclusively framed by the interaction between social conditions and material reality. The experimental nature of self-building adds a processual dimension to the dialectical constitution of residents' aspirations, as had been established by Preece et al (2019). This adds an element of contingency into the relation between conditions and aspirations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also demonstrated that literature mapping can be a crucial stage towards evidence reviews in that it can formulate new research questions as well as delineate subgroups of studies for analysis. Indeed, our literature mapping was mobilised to inform related evidence reviews (Preece, Crawford, McKee, Flint, & Robinson, 2019) and to offer contextual information in other reviews (Lenoel, Matsu, & Naisbitt, 2018). Like any sound methodology, systematic literature mapping can thus contribute to the advancement of housing knowledge or theory.…”
Section: Discussionmentioning
confidence: 99%
“…The affordability of housing is a pressing international concern (Preece et al, 2019), and 'one of the most prominent domestic public policy issues' in England (Joyce et al, 2017, p. 5). However, as Bramley (2012, p. 134) argues, affordability is invoked in a wide variety of contexts, with different meanings and connotations.…”
Section: Affordability Conditionality and Welfare Reformmentioning
confidence: 99%